Diphenhydramine as an Alternative Local Anesthetic Agent - Pavlidakey, Peter G. (Matrix Medical Communications, 2009)
Patients who present with a history of “allergy” to local anesthetics are common in clinical practice. Injectable 1% diphenhydramine is a safe, inexpensive, and effective local anesthetic for simple dermatological procedures in patients who report “caine” allergies. Utilizing this agent permits the dermatologist to operate at the time of the initial visit and schedule a referral to the allergist for definitive sensitivity testing at the patient’s convenience.